Integration, Specialization, and Adjustment. - Krugman, P; Venables, A (1996)
The paper considers the location of two industries in two countries. Both industries are imperfectly competitive, producing goods for final consumption and use as intermediates. Intermediate usage creates cost and demand linkages between firms, encouraging industrial agglomeration. With high trade barriers each industry operates in both locations in order to supply final consumers. At lower trade barriers agglomeration forces dominate and each industry concentrates in a single location. Economic integration therefore induces agglomeration. There are long run gains from integration, but during the adjustment process some of the labour force may suffer lower real wages as relocation of industry occurs.